Canadian Cardiovascular Society Position Statement on Familial Hypercholesterolemia: Update 2018 - Brunham, Liam R.; Ruel, Isabelle; Aljenedil, Sumayah; Rivière, Jean-Baptiste; Baass, Alexis; Tu, Jack V.; Mancini, G.B. John; Raggi, Paolo; Gupta, Milan; Couture, Patrick; Pearson, Glen J.; Bergeron, Jean; et al. (Canadian journal of cardiology, 2018)
Familial hypercholesterolemia (FH) is the most common monogenic disorder causing premature atherosclerotic cardiovascular disease. It affects 1 in 250 individuals worldwide, and of the approximately 145,000 Canadians estimated to have FH, most are undiagnosed. Herein, we provide an update of the 2014 Canadian Cardiovascular Society position statement on FH addressing the need for case identification, prompt recognition, and treatment with statins and ezetimibe, and cascade family screening. We provide a new Canadian definition for FH and tools for clinicians to make a diagnosis. The risk of atherosclerotic cardiovascular disease in patients with “definite” FH is 10- to 20-fold that of a normolipidemic individual and initiating treatment in youth or young adulthood can normalize life expectancy. Target levels for low-density lipoprotein cholesterol are proposed and are aligned with the Canadian Cardiovascular Society guidelines on dyslipidemia. Recommendation for the use of inhibitors of proprotein convertase kexin/subtilisin type 9 are made in patients who cannot achieve therapeutic low-density lipoprotein cholesterol targets on maximally tolerated statins and ezetimibe. The writing committee used the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) methodology in the preparation of the present document, which offers guidance for practical evaluation and management of patients with FH. This position statement also aims to raise awareness of FH nationally, and to mobilize patient support, promote knowledge translation, and availability of treatment and health care resources for this under-recognized, but important medical condition. L’hypercholestérolémie familiale (HF) est la maladie monogénique la plus courante à l’origine d’une pathologie cardiovasculaire athéroscléreuse précoce. Elle touche 1 personne sur 250 dans le monde et, chez la plupart des quelque 145 000 Canadiens atteints selon les estimations, demeure non diagnostiquée. Dans cet article, nous présentons une mise à jour de l’énoncé de position de la Société canadienne de cardiologie de 2014 sur la HF soulignant la nécessité du diagnostic rapide, du traitement par des statines et de l’ézétimibe et du dépistage familial en cascade. Nous proposons une nouvelle définition canadienne de la HF et des outils diagnostiques à l’intention des cliniciens. Le risque de maladie cardiovasculaire athéroscléreuse chez les patients ayant reçu un diagnostic de HF est de 10 à 20 fois supérieur à celui d’une personne normolipidémique, et l’instauration d’un traitement chez les jeunes ou les jeunes adultes peut normaliser leur espérance de vie. Des valeurs cibles du taux de cholestérol à lipoprotéines de basse densité conformes aux lignes directrices sur la dyslipidémie de la Société canadienne de cardiologie sont proposées. L’administration d’inhibiteurs de la proprotéine convertase kexine/subtilisine de type 9 est recommandée chez les patients qui ne parviennent pas à atteindre les cibles thérapeutiques en matière de cholestérol à lipoprotéines de basse densité aux doses maximales tolérées de statine et d’ézétimibe. Le comité de rédaction a utilisé la méthodologie GRADE (Grading of Recommendations, Assessment, Development, and Evaluation) pour élaborer le présent document, qui contient des recommandations pratiques pour l’évaluation et la prise en charge des patients atteints de HF. Cet énoncé de position a également pour objectifs de promouvoir la sensibilisation à la HF à l’échelle nationale, l’offre de mesures de soutien aux patients, l’application des connaissances et la disponibilité des ressources en matière de traitement et de soins de santé pour cette affection dont l’importance a été longtemps négligée.